2018
DOI: 10.1002/asia.201800551
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized NMR Spectroscopy: d‐DNP, PHIP, and SABRE Techniques

Abstract: The intensity of NMR signals can be enhanced by several orders of magnitude by using various techniques for the hyperpolarization of different molecules. Such approaches can overcome the main sensitivity challenges facing modern NMR/magnetic resonance imaging (MRI) techniques, whilst hyperpolarized fluids can also be used in a variety of applications in material science and biomedicine. This Focus Review considers the fundamentals of the preparation of hyperpolarized liquids and gases by using dissolution dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
251
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 232 publications
(259 citation statements)
references
References 205 publications
(422 reference statements)
0
251
0
8
Order By: Relevance
“…[2,3] This drug is approved by the regulating agencies in the US, Canada, and Europe, andi ti sm arketed as Ampyraa nd Fampyra.T he distribution of the drug inside the body,t he biochemicalpathways of its transformation,aswellasits metabolic profile are important information for determining the effectivenesso ft he drug. [7][8][9][10][11] Parahydrogen servesa sasourceo fh yperpolarization in this method, and two SABRE approaches have been developed. [4] This is due to the fact that populationdifferenceo fn uclear spin states (termed nuclear spin polarization P)i ss mall.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] This drug is approved by the regulating agencies in the US, Canada, and Europe, andi ti sm arketed as Ampyraa nd Fampyra.T he distribution of the drug inside the body,t he biochemicalpathways of its transformation,aswellasits metabolic profile are important information for determining the effectivenesso ft he drug. [7][8][9][10][11] Parahydrogen servesa sasourceo fh yperpolarization in this method, and two SABRE approaches have been developed. [4] This is due to the fact that populationdifferenceo fn uclear spin states (termed nuclear spin polarization P)i ss mall.…”
mentioning
confidence: 99%
“…The directu se of at hermally polarized signal of 15 Nn uclei for in vivo MRI applicationsi sv ery challenging because of the very low natural abundance of the 15 Ni sotope (0.365 %) and the lowerg yromagnetic ratio of 15 Nn uclei compared to 1 H ( % 1:10), resulting in low detection sensitivity.Asaresult, alimited number of 15 NM RI studies with non-isotopically enriched molecules were reported to date. [7][8][9][10][11] Parahydrogen servesa sasourceo fh yperpolarization in this method, and two SABRE approaches have been developed. [7][8][9][10][11] Parahydrogen servesa sasourceo fh yperpolarization in this method, and two SABRE approaches have been developed.…”
mentioning
confidence: 99%
“…We simulated the relaxation kinetics of af ree 15 Ns ubstrate by using Equation (13) with the following parameters:t he values of T 1 for the bound substrates, substrates in solution and hydride protons were 10, 60 and1s, respectively (see Tables S1-S4 in the Supporting Information), k d = 50 s À1 , k a = 1000 m À1 s À1 , k ex = 200 m À1 s À1 , W out = 10 s À1 ,H 2 ½ = 50 mm, f pH 2 = 25 %a nd S 0 ½ = 100 mm for three different concentrations of Ir 0 ½ :3 0, 10 and 1mm.T he para enrichment fraction f pH2 of 25 %m eans that hydrogen gas at room temperature thermal equilibrium was supplied to the system;t hus, no pH 2 -induced hyperpolarization occurred. The relaxation was investigated at two different static magnetic fields: B = 1Tand 1 mT ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this work we calculated the 15 Np olarizationo ft he free substrate as af unction of H 2 ½ and k ex ( Figure 7A)a nd H 2 ½ and W out ( Figure 7B). We found that the polarization level can be strongly improvedb yi ncreasing the rate of H 2 exchange with the transient complex, that is, the product H 2 ½ k ex [ Figure 7A,r eaction (3)].…”
Section: Sabre-sheath:ph 2 Exchangementioning
confidence: 99%
See 1 more Smart Citation